Issues and challenges faced by Brazilian adults to learn English - Mira, Fabiana de (Revista Liberato, 2023)
In Brazil, all students in regular schools have English classes at some point in their lives, most of them usually start in 6th grade. However, when teachers and job interviewers ask about their knowledge, the answers show that they cannot speak, read, or write the language well. The Brazilian Educational Law of Guidelines and Bases requires a “foreign language” which may be Spanish, for example. When they become adults, it is essential to speak a second language to get better job opportunities. This study has investigated some aspects of English teaching/learning in Brazil, which may encourage many people to come to the U.S. to learn. Nowadays, there is a big wave of Brazilians coming to study English as an additional language. The study has mainly focused on adult Brazilian English learners living in the U.S. and it has identified the profile of these adult students, their motivation, their challenges, as well as issues about age, affection, and beliefs related to this topic.